2019
DOI: 10.5586/aa.1770
|View full text |Cite
|
Sign up to set email alerts
|

Breeding and agronomic approaches for the biofortification of zinc in wheat (Triticum aestivum L.) to combat zinc deficiency in millions of a population: a Bangladesh perspective

Abstract: The World Health Organization (WHO) has estimated that around 2 billion people across the globe are suffering from “hidden hunger”, where 815 million are under malnutrition. The major essential elements for humans are Fe, Zn, I, Se, Ca, F, and also vitamins. Among them, Zn is considered in the fifth place leading to causes of several deficiency diseases. At least one-third of the population in the world is facing Zn deficiency including around 450,000 children under the age of five. Vitamin A, Fe, and Zn defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…For Zn, although this general consensus lacks, many studies may have suggested the application of zinc sulfate (ZnSO 4 -7H 2 O) as either a soil application before sowing (50 kg Zn ha −1 ) or a foliar application at the start of flowering (4-8 kg Zn ha −1 ), each one alone or in combination. There are other forms of Zn used, like ZnEDTA, which might be more efficient but its higher cost made it less accessible to farmers (Cakmak 2008;Das et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For Zn, although this general consensus lacks, many studies may have suggested the application of zinc sulfate (ZnSO 4 -7H 2 O) as either a soil application before sowing (50 kg Zn ha −1 ) or a foliar application at the start of flowering (4-8 kg Zn ha −1 ), each one alone or in combination. There are other forms of Zn used, like ZnEDTA, which might be more efficient but its higher cost made it less accessible to farmers (Cakmak 2008;Das et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Foliar applications of fertiliser in the grain maturation stage, near harvesting appears to be very efficient as starchy endosperm absorption is up to three-fold and the phytate concentration is at a sub-optimal level (Velu et al 2014). Das et al (2019) reported that an optimal time for increasing grain mineral concentration was achieved with a combination of foliar application of Zn after anthesis, plus a soil mineral application (Das et al 2019). Knez et al (2018) developed Zn biofortified wheat grain by a foliar application of 1.5 L ha −1 ZnSO 4 during the mid-vegetative growth stage followed by 2 L ha −1 ZnSO 4 two weeks after flowering.…”
Section: The Success Of Agronomic Researchmentioning
confidence: 99%
“…One of the ways to improve the technology of crop cultivation is to use chemicals to control biological processes with the help of plant growth regulators (Das et al, 2019;Moumita et al, 2019). e physiologically active substances of plant growth regulators are both the object and tool of the biotechnologies used in the selection of high-yielding crop cultivars.…”
Section: Introductionmentioning
confidence: 99%